Early clinical features in Systemic Lupus Erythematosus: can they be used to achieve earlier diagnosis?: a risk prediction model - Rees, Frances; Doherty, Michael; Lanyon, Peter; Davenport, Graham; Riley, Richard D.; Zhang, Weiya; Grainge, Matthew J. (Wiley, 2017)
OBJECTIVES: 1) To compare the primary care consulting behaviour prior to diagnosis of people with Systemic Lupus Erythematosus (SLE) with controls, 2) to develop and validate a risk prediction model to aid earlier SLE diagnosis.